2011
DOI: 10.1021/ie200055s
|View full text |Cite
|
Sign up to set email alerts
|

On the Gradient Diffusion Hypothesis and Passive Scalar Transport in Turbulent Flows

Abstract: A discussion of modeling passive scalar transport in turbulent flows is given. Several methods employed to close the scalar-flux term ⟨u′ϕ′⟩ that arises during Reynolds averaging are provided. Alternatives and improvements to the gradient diffusion hypotheses are addressed, most notably, the need for an alternative to the global constant turbulent Schmidt and Prandtl numbers. The reader is given a brief history covering methods used to predict turbulent Schmidt and Prandtl numbers, along with recommendations f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(32 citation statements)
references
References 29 publications
0
32
0
Order By: Relevance
“…These results confirmed that one single value of Sc t is unable to represent the physical processes in the entire domain and that Sc t may need to be calibrated on a case by case basis. Thus, it would be of interest to better represent the effects of hydrodynamic unsteadiness and turbulence anisotropy on the scalar transport [25] through refined turbulence and algebraic GDH models as highlighted by Combest et al [97]. For the contact tank, it would be interesting to determine whether inaccuracies can be attributed solely to the inadequacy of the particular turbulence model (in this case, the standard k-ε) chosen or whether an improved calculation of the turbulent diffusivity, e.g., by a locally-varying value of Sc t or a departure from the standard GDH would allow more reliable, ideally uncalibrated, predictions.…”
Section: Discussionmentioning
confidence: 99%
“…These results confirmed that one single value of Sc t is unable to represent the physical processes in the entire domain and that Sc t may need to be calibrated on a case by case basis. Thus, it would be of interest to better represent the effects of hydrodynamic unsteadiness and turbulence anisotropy on the scalar transport [25] through refined turbulence and algebraic GDH models as highlighted by Combest et al [97]. For the contact tank, it would be interesting to determine whether inaccuracies can be attributed solely to the inadequacy of the particular turbulence model (in this case, the standard k-ε) chosen or whether an improved calculation of the turbulent diffusivity, e.g., by a locally-varying value of Sc t or a departure from the standard GDH would allow more reliable, ideally uncalibrated, predictions.…”
Section: Discussionmentioning
confidence: 99%
“…The concern expressed by Combest, Ramachandran & Dudukovic (2011) regarding the lack of availability of reliable values of the turbulent Prandtl number (Pr T ), later addressed in Darisse, Lemay & Benaïssa (2013a), is but one implication. In spite of that, reliable measurements of the passive scalar field of round jets evolving in still air (without a co-flow) are few and far between (Gouldin et al 1986).…”
mentioning
confidence: 99%
“…However, it is clearly seen that the chemical source terms are important at x/d = 10 compared with the production terms because of the large reaction rate in this region. In the eddy viscosity model (Combest et al 2011), the Reynolds stress is given by…”
Section: Resultsmentioning
confidence: 99%
“…One of the most practical and widely used models for u i γ α is the gradient diffusion model (e.g. Tominaga & Stathopoulos 2007;Combest, Ramachandran & Dudukovic 2011), in which u i γ α is modelled by…”
Section: Introductionmentioning
confidence: 99%